REPRESENTATION OF DEFENSE MECHANISMS OF A BROKEN-HEARTED WOMAN: A CASE STUDY OF OLIVIA RODRIGO’S ALBUM SOUR (2021) - Anggi Saidah Rahim Purnama Putri; Todo Sibuea (DIALEKTIKA: JURNAL BAHASA, SASTRA DAN BUDAYA, 2025)
This research examines the lyrics of Olivia Rodrigo’s SOUR album through Michael Riffaterre’s semiotic framework and Anna Freud’s defense mechanisms, complemented by Vaillant’s hierarchy. The research aims to identify both literal and connotative meanings by applying heuristic and hermeneutic readings, while also uncovering the unconscious emotions represented through figurative devices such as metaphor, irony, imagery, symbolism, and rhetorical expressions. Furthermore, the study explores the defense mechanisms reflected in the lyrics as psychological responses to emotional experiences such as heartbreak, jealousy, denial, and loss of self-worth. The findings indicate that the lyrics in SOUR employ intricate figurative language that functions as an expressive medium for emotional complexity and demonstrate the presence of defense mechanisms across immature, neurotic, and mature levels. These results show that popular music lyrics can serve as a rich academic object for linguistic and psychological inquiry, contributing to the advancement of literary studies, semiotics, and psychological criticism within the landscape of contemporary popular culture. Keywords: ​Unconscious emotions, defense mechanism, figurative language, semiotics.